Normative Observations on the International Value-Added Chain and Strategic Groups - Kogut, Bruce (Journal of International Business Studies, 1984)
The formulation of strategy can be fruitfully viewed as placing bets on certain markets and on certain links of the value-added chain. The key to understanding a global strategy is to locate how competitive positions in one national market change the economics for entry into other countries and into other product lines. This article argues that global strategies succeed by creating certain economies along and the between value-added chains and by designing marketing programs that adapt products to national needs and yet exploit these upstream economies. Two major conclusions are that a company can compete in different strategic groups across countries and that a hallmark feature of a global strategy is the creation of operational flexibility to benefit from uncertainty.